Parotid Gland Swelling as an Initial Presentation of Multiple Myeloma: A Case Report - Dewangan, Ankita; Singh, Swati; Singh, Jitendra; Kumar, Nilesh; Kumar, Kailash (Cardiovascular & Haematological Disorders - Drug Targets, 2022)
Introduction: Parotid swellings are commonly encountered in ENT clinics, the cause of which could range from neural conditions, endocrine problems, vitamin deficiencies, and sialadenitis, which may even be a manifestation of an underlying systemic disease. Multiple myeloma represents a clonal proliferation of plasma cells and is a condition in which a parotid swelling might be present, although very uncommon. Case presentation: We report a case of a 60-year-old female who was presented with unilateral parotid swelling, which led to a diagnosis of multiple myeloma based on the investigations. Conclusion: Various imaging modalities are currently available to assess the extent of the swelling and evaluate the soft tissue and osseous involvement. The clinician must have a rigorous insight into the several clinical manifestations and the sites of involvement of the different conditions to make a proper diagnosis.
Keywords: ent